Analysis of determinant factors of ARI incidents in home industry workers refining essential oil from patchouli plant in Konawe District - Setriyalin Putri Amir; La Ode Muhamad Sety; Devi Savitri Effendy (Indonesian Journal of Health Science, 2026)
ARI or Acute Respiratory Tract Infection is an infection that attacks the upper and lower respiratory tract that lasts up to 14 days caused by viruses and bacteria. Home industry workers are often exposed to total dust and wood burning smoke which is consistently associated with increased ARI symptoms and decreased lung function. The purpose of this study was to analyze the determinants of ARI incidence in patchouli oil refining home industry workers in Konawe District. The method used in this study was an analytical observational with individual observation units using a cross-sectional design with a total sampling technique. The results showed that there was a significant relationship between the level of knowledge (p-value = 0.008), smoking habits (p-value = 0.016), use of firewood (p-value = 0.022), duration of exposure (p-value = 0.003), and distance from the worker's house (p-value = 0.005), with the incidence of ARI. And there was no significant relationship between the use of PPE masks (p-value = 0.877) with the incidence of ARI. Therefore, local governments are expected to improve guidance and supervision of work environment conditions, provide education and training regarding occupational safety and health (OSH), especially regarding the prevention of ARI.